Improving Ramayana Story Writing Skills by Applying the Problem Based Learning Model Assisted by Snakes and Ladders Formative Assessment Media in Class VII E Students of SMP Negeri 27 Semarang - Herfianingtyas, Devika -; Marsini, Marsini; Fuadhiyah, Ucik (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2024)
This research was motivated by the low writing skills of the majority of class VII E students at SMP Negeri 27 Semarang in learning Javanese on the Ramayana story material. The aim of conducting research is to describe the application of the Problem Based Learning model assisted by the formative assessment media Snakes and Ladders in improving students' writing skills in learning Javanese on the Ramayana Story material in class VII E of SMP Negeri 27 Semarang. This research uses the Classroom Action Research (PTK) method which consists of two cycles, each cycle includes planning, implementation, observation and reflection. Data was collected through observation, assessment of written Ramayana stories, questionnaires, field notes, documentation, and interviews. Data analysis was carried out using descriptive analysis techniques for qualitative and quantitative data. Research shows that the average score for writing Ramayana Stories in pre-action was 64.41, cycle I was 73.97, and in cycle II was 81.91. The percentage of students' completion of Ramayana Story writing skills from pre-test to the end of cycle I increased from 47.06% to 64.71%, then in cycle II it increased to 79.41%. Based on these scores, it can be concluded that from before the action to after the action, the average score of students' Ramayana Story writing skills has increased by 17.50, namely from a score of 64.41 to 81.91. The learning process in cycle I ran more conducively and better than before, and there were positive changes in student behavior. In cycle II, class conditions are more conducive, learning becomes fun and meaningful for students..